(untitled) (Polifonia, 1995)
ABSTRACT: Teh rise of the novel in eighteenth-century England foregrounded woman as protagonist of the new literacy genre which, like much of the intellectual production of the period, took an unprecedejnted interest in women’s nature and position. This article intends to discuss the representation of women in the 18th century English novel, based on two assumptions: firstly, the feminine was a cultural and social construction rather than a natural quality; secondly, thye new genre did not simply reflect values but helped to create them.